(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
In the context of modern educational reforms and competency-based learning, the development of reflective skills has become one of the key priorities in pedagogy and psychology. Reflective skills enable learners to analyze their own cognitive processes, evaluate their actions, and improve future performance based on self-awareness and critical thinking.